When a Volunteer Fits: Motivational Effects through the Self-Determination Theory - Holtrop, Djurre; Gagné, Marylène; Dunlop, Patrick; Soo, Christine (2019)
Purpose: Volunteers give their time freely, in contrast to employees who also work for financial reasons. Therefore, feelings of fit may be even more important to retain volunteers than for employees. Yet, fit has scarcely been investigated in volunteers. Using a two-wave survey study, we investigated the consequences of complementary (i.e., demands-ability and needs-supplies) volunteer fit through the lens of the Self-Determination Theory. Specifically, we investigated the effect of fit on volunteer retention through changes in need satisfaction (feeling related, competent, and autonomous) and motivation (amotivation, extrinsic, and autonomous). Design: One year apart, 612 volunteers completed two largely identical surveys. These surveys included adapted measures of 1) demands-abilities and needs-supplies fit, 2) psychological need satisfaction, 3) volunteer motivation, and 4) intentions to keep volunteering. Results: Overall, using regression and relative weight analyses, the results showed that increases in demands-abilities (R2=.03) and need-supplies (R2=.02) fit both led to small increases in need satisfaction. Next, increases in need satisfaction were related to decreases in amotivation (R2=.05), no change in extrinsic motivation (R2=.01), and increases in autonomous motivation (R2=.04). Finally, increases in motivation we barely related to intentions to remain a volunteer (respectively R2=.05, .01, and .02). Limitations/Implications: The present study indicates that changes in volunteers’ demands-abilities and need-supplies fit lead to very small changes in important individual and organisational outcomes. Therefore, improving fit may not be an effective way to improve volunteer retention. Future research could study volunteer fit with motivation frameworks that are specific to volunteers, such as the ‘volunteer functions’.